2011
DOI: 10.1111/j.1464-410x.2011.10193.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of testosterone administration to men with prostate cancer is unpredictable: a word of caution and suggestions for a registry

Abstract: What’s known on the subject? and What does the study add? Very little is known on the effect of T in men with untreated PCa. There are only two small series (including the present one) available that comprise less than 25 men with PCs receiving TTh. It raises a warning that testosterone administration to men with PCa is not always safe, that current precautions should be maintained, and that only an international registry would provide prompt answers to these issues. To assess the evidence for the concept tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 22 publications
(23 reference statements)
2
50
0
2
Order By: Relevance
“…Morgentaler et al [32] observed 13 patients with known PCa, who were treatment naïve and had clinically significant hypogonadism during TRT for a median of 2.5 years, and did not find a single example of local or systemic progress. Morales [33] reported on 7 men with untreated PCa and hypogonadism on TRT, 5 of whom had low-risk disease. The report describes 4 different PSA scenarios, 1 stable course and 3 distinct profiles of progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morgentaler et al [32] observed 13 patients with known PCa, who were treatment naïve and had clinically significant hypogonadism during TRT for a median of 2.5 years, and did not find a single example of local or systemic progress. Morales [33] reported on 7 men with untreated PCa and hypogonadism on TRT, 5 of whom had low-risk disease. The report describes 4 different PSA scenarios, 1 stable course and 3 distinct profiles of progression.…”
Section: Discussionmentioning
confidence: 99%
“…The report describes 4 different PSA scenarios, 1 stable course and 3 distinct profiles of progression. Thus, Morales [33] advises others to be cautious and advocates for an international registry to identify risk factors relevant for hormonal treatment in men with PCa. The guidelines of the European Association of Urology [34] on male hypogonadism see PCa as a contraindication for testosterone substitution.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, limited reports of testosterone use in hypogonadal men on active surveillance protocols appear promising [Morales, 2011;Morgentaler et al 2011]. Yet one must emphasize the data for TRT in men with a history of prostate cancer are without randomized or placebo controlled trials and should be interpreted with caution.…”
Section: Controversies and Riskmentioning
confidence: 99%
“…12,13 Similar observations have been reported in patients with cancers confined to the gland. 14,15 The reasons remain conjectural, but range from the effect of estrogens (due to an age-related differential) in the aromatization of testosterone on the nuclear androgen receptor (AR) and the length of the CAG repeats to the lack of prostatic uptake of exogenous testosterone. The relevant point here is that there may be substantial inter-individual responses to changes in the hormonal environment of men with PCa and we should be wary of oversimplifications and generalizations.…”
mentioning
confidence: 99%
“…It is evident that only a countrywide registry would provide the power to address some of the pressing issues related to testosterone administration to men with PCa. A wider effort, such as a North American (or even better, a global registry) 15 offers a better opportunity to reach credible conclusions within a shorter time context. Randomized, placebo-controlled studies, 18 although ideal, at this time remain utopian.…”
mentioning
confidence: 99%